Austin Powers triple feature [videorecording (Blu-Ray)] : Austin Powers, international man of mystery ; Austin Powers, the spy who shagged me ; Austin Powers in Goldmember - Myers, Mike, 1963-; Knowles, Beyonce; Green, Seth; York, Michael; Caine, Michael; Wagner, Robert; Graham, Heather; Hurley, Elizabeth; Rogers, Mimi; Todd, Suzanne; Moore, Demi; Todd, Jennifer; et al. (New Line Productions : Distributed by Warner Home Video, 2012)
International Man of Mystery : Frozen in the 60s, British secret agent Austin Powers is thawed back into action to once again battle his archenemy Dr. Evil. The Spy Who Shagged Me : Intent on world domination, diabolical genius Dr. Evil travels back to 1969 and steals Austin's "mojo". Now Austin must return to the swingin' sixties, recover his mojo and stop his nemesis from liquidating the world. Goldmember : The "sshhh!" hits the fan when Dr. Evil and Mini-Me escape from prison. Joining forces with superfreaky Goldmember, they kidnap Austin's father, master spy Nigel Powers in a dastardly time-travel scheme to take over the world. So Austin cruises to 1975 and teams up with Foxxy Cleopatra to stop Dr. Evil and Goldmember from their mischievous mayhem.